2021
DOI: 10.3389/fgene.2021.706260
|View full text |Cite
|
Sign up to set email alerts
|

Networks of Networks: An Essay on Multi-Level Biological Organization

Abstract: The multi-level organization of nature is self-evident: proteins do interact among them to give rise to an organized metabolism, while in the same time each protein (a single node of such interaction network) is itself a network of interacting amino-acid residues allowing coordinated motion of the macromolecule and systemic effect as allosteric behavior. Similar pictures can be drawn for structure and function of cells, organs, tissues, and ecological systems. The majority of biologists are used to think that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 127 publications
0
12
0
Order By: Relevance
“…As self-organizing systems, scale-free networks are composed of self-repeating patterns (fractals) across diverse length scales . Curiously, the same principles are also applicable to individual proteins because the spatiotemporal structural organization can be envisaged as an intraprotein network, wherein the individual amino acids participate in interactions that are transient or stable . In fact, it was recently shown that a protein molecule may be visualized as a complex system existing as a dynamic, multilevel network of networks analogous to a nesting doll (Matryoshka).…”
Section: Idps Self-organization and Scale-free Networkmentioning
confidence: 99%
“…As self-organizing systems, scale-free networks are composed of self-repeating patterns (fractals) across diverse length scales . Curiously, the same principles are also applicable to individual proteins because the spatiotemporal structural organization can be envisaged as an intraprotein network, wherein the individual amino acids participate in interactions that are transient or stable . In fact, it was recently shown that a protein molecule may be visualized as a complex system existing as a dynamic, multilevel network of networks analogous to a nesting doll (Matryoshka).…”
Section: Idps Self-organization and Scale-free Networkmentioning
confidence: 99%
“…Subsequently, we examined the topological features of the PD-EASR network. This revealed that the PD-EASR network is a scale-free network, which is a common characteristic of biological networks (Uversky and Giuliani, 2021). Also, to fully understand the functional links between PD-related genes and EASR genes, we performed enrichment analysis for the core PD-EASR network, representing its function in neuron death (GO:0070997).…”
Section: Discussionmentioning
confidence: 99%
“…Grimace scales have been developed for a range of different species including rats, rabbits, and horses and can provide a useful and rapid method both for pain detection and in determining whether an-Alessandro Giuliani (Istituto Superiore di Sanità -ISS, Italy) introduced the concept of Reduction from a wide theoretical perspective. He argued that the behavior of biological systems emerges from the correlation of different players at all biological and organization levels from molecules to ecosystems (Uversky and Giuliani, 2021). This implies that there is no single privileged level of explanation (prediction) for biologically relevant endpoints.…”
Section: Meeting Reportmentioning
confidence: 99%